A digital twin-based approach for the management of geometrical deviations during assembly processes. (January 2021) - Grégorio, Jean-Loup; Lartigue, Claire; Thiébaut, François; Lebrun, Régis
Highlights: A hybrid representation for the digital twin for assembly processes is proposed. This representation includes as-built, as-designed and interface components. A geometrical skeleton materializes the structure-functional model of the product and allows to take geometrical deviations into account. A method to update this virtual representation from 3D acquisition data using machine-learning is proposed. The proposed digital twin is able to simulate and optimize n + 1 assembly operations by updating the geometry of interface components. Abstract: The recent transformation in the aeronautical industry gives new prospects in the field of product geometry assurance. These include, in particular the creation of sophisticated virtual models, or digital twins, which can reflect the as-built geometry of physical products and optimize the assembly operations consequently. One of the current obstacles to the implementation of such digital twins is linked to the difficult transition from a conceptual model to a usable virtual representation. In this article, we present the hybrid representation of a product which is capable of integrating the different states of the components at each step of the assembly process. We propose a method to update the virtual representation of already assembled components, in order to include the position and orientation deviations of their surfaces. The B-Rep model of each component is updated from data acquired during the assembly of the product. The various steps of this update, and its associated tools are discussed in the article. Based on the knowledge of the as-built component geometry, the geometry of the yet-to-be-assembled components is adapted so that the final product complies with the functional requirements. To this end, we also discuss a formalism to model the product's functional information and to translate it at a geometrical level thanks to an assembly skeleton.